Archaeological excavations and reconstructions of disappeared archaeological heritage (based on excavations in North-Western Russia) - Mazurkevich, Andrey; Dolbunova, Ekaterina; Ottonello, Luca (Vita Antiqua, 2018)
Archaeological excavations allow us to investigate archaeological heritage, but at the same time, they leadto its destruction. Multi-layer archaeological sites, which were settled during multiple stages of occupation andinclude several cultural horizons, represent a number of events. Their “decoding” is possible only by applicationof various methods – archaeological, natural-scientific, as well as the use of virtual modelling. Archaeologicalexcavations allow tracing of different stages of people inhabitation, whereas digital reconstruction gives thepossibility to visualize these stages and reconstruct disappeared archaeological heritage, destroyed in thecourse of people activity during long time. In this case archaeological field documentation, precise recording,further researches and reconstructions based on them are tightly interrelated. Combination ofdifferent methods gives the potential of preservingand telling the stories in a way that was never possiblebefore; creating time pictures of explorableareas with an unprecedented level of detail byusing animation and reconstruction methods,which could finally contribute a lot to interpretationof the sites. Computer-based visualisation seeks torepresent the existing state, an evidence-basedrestoration or a hypothetical reconstruction of acultural heritage object or site, and the extent andnature of any factual uncertainty. Such a combination of methodswas applied during researches of Neolithic sites in North-Western Russia, in Dnepr-Dvina region.Analysis made in Dnepr-Dvina areaallowed making virtual reconstructions of severalsites, tracing particularities of artefacts depositionand cultural layers formation, identifying particularitiesof paleoenvironmental situation duringdifferent periods and finally visualization ofancient sites. SNF-SCOPES project "Network in Eastern European Neolithic and Wetland Archeology for the improvement of field techniques and dating methods" (NEENAWA)